Politiques urbaines pour la mise en récit d’une ville moyenne périphérisée en décroissance : L’exemple de Montluçon - Mikel Agirre-Maskariano (Belgeo)
Urban decline has become a major issue for many small- and middle-sized cities faced with considerable processes of peripherisation in an era of neoliberal globalisation. The paper deals with the urban and political strategies established in the French city of Montluçon, distant from metropolitan areas. The paper is based on research materials resulting from semi-directive interviews, focusing on the analysis of the materialisation of dominant urban narratives at local scale. The paper argues that far from accepting the reality, the actors concerned always tend to consider urban decline as an anomaly contrary to the hegemonic order of growth. The study shows that in attempting to become competitive, the city has engaged into a process of urban transformation aiming at highlighting an imaginary bound to its quality of life. Local policy uses the renewal of the urban space as a marketing strategy in order to project a new image of the city compliant with dominant narratives, which nevertheless failed to generate the expected growth.